DIAGNOSTIC ACCURACY OF QUANTITATIVE WASHOUT CALCULATED ON TRIPHASIC CT SCAN FOR DIAGNOSIS OF HEPATOCELLULAR CARCINOMA KEEPING HISTOPATHOLOGY AS GOLD STANDARD: Quantitative Washout Calculated on Triphasic CT Scan - Hameed, Dr Huma; Nafees, Muhammad; Sameeuddin, Syed (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the diagnostic accuracy of quantitative washout calculated on Triphasic CT scan for diagnosis of hepatocellular carcinoma keeping histopathology as gold standard. Study Design: Descriptive, cross-sectional validation study. Place and Duration of Study: Armed Forces Institute of Radiology and Imaging Rawalpindi, from Feb 2016 to Aug 2016. Material and Methods: A total of 132 patients of either sex with age in range 15-75 years diagnosed to have focal liver lesion on ultrasonography were included. Patients in whom focal lesion was cyst or abscess, patients with renal failure, pregnancy or known sensitivity to contrast agents were excluded. All the patients then underwent Triphasic CT scan to calculate quantitative washout on delayed phase. The lesion was diagnosed as HCC if percent attenuation ratio was >107. The results were later correlated with histopathology findings. Results: Mean age was 49.75 ± 15.18 years. Out of 132 patients, 86 (65.15%) were males and 46 (34.85%) were females with ratio of 2:1. In Triphasic CT scan positive patients, 78 were True Positive and 09 were False Positive. Among 45, Triphasic CT scan negative patients, 07 were False Negative where as 38 were True Negative. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of quantitative washout calculated on Triphasic CT scan for diagnosis of hepatocellular carcinoma was 91.76%, 80.85%, 89.66%, 84.44% and 87.88% respectively. Conclusion: This study concluded that quantitative washout calculated on Triphasic CT scan is a highly sensitive and accurate non-invasive modality for diagnosis of hepatocellular carcinoma.